2008
DOI: 10.1080/13607860802120938
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in aged Chinese patients with silicosis

Abstract: High prevalence of depressive symptoms was found in patients with silicosis. Respiratory symptoms, physical function and pulmonary functions were associated with depressive symptoms. Our findings provide evidence for physicians to screen for depressive symptoms in patients with silicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
2
17
0
4
Order By: Relevance
“…Previous studies in patients with pneumoconiosis and other chronic respiratory diseases revealed that these diseases had affected the quality of life of patients. Our results accord with these findings (3,14,23,24).…”
supporting
confidence: 83%
See 4 more Smart Citations
“…Previous studies in patients with pneumoconiosis and other chronic respiratory diseases revealed that these diseases had affected the quality of life of patients. Our results accord with these findings (3,14,23,24).…”
supporting
confidence: 83%
“…Psychiatric disorders were found to be more frequent in patients with pneumoconiosis than in the normal population in a study which focused on the relationship between silicosis and depression (23). It has been established that elderly silicosis patients have high rates of depression co-morbidity (3,25). In our study, we compared young male silicosis patients and healthy controls, and the results obtained were similar to previous reports.…”
supporting
confidence: 79%
See 3 more Smart Citations